Navigating the Ethical Maze: Key Issues in AI-Driven Medical Decisions - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into clinical practice marks a transformative era in healthcare. From sophisticated diagnostic imaging analysis...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care